Review and Harmonization of the Life-Cycle Global Warming Impact of PV-Powered Hydrogen Production by Electrolysis - Kanz, Olga; Bittkau, Karsten; Ding, Kaining; Rau, Uwe; Reinders, Angèle (Frontiers in Electronics, 2021)
This work presents a review of life-cycle assessments (LCA) of hydrogen electrolysis using power from photovoltaic (PV) systems. The paper discusses the assumptions, strengths and weaknesses of 13 LCA studies and identifies the causes of the environmental impact. Differences in assumptions of system boundaries, system sizes, evaluation methods, and functional units make it challenging to directly compare the Global Warming Potential (GWP) resulting from different studies. To simplify this process, 13 selected LCA studies on PV-powered hydrogen production have been harmonized following a consistent framework described by this paper. The harmonized GWP values vary from 0.7 to 6.6 kg CO2-eq/kg H2 which can be considered a wide range. The maximum difference between the original and harmonized GWP results of a study is 1.5 kg CO2-eq/kg H2. Yet even the highest GWP of this study is over four times lower than the GWP of grid-powered electrolysis in Germany. Due to the lack of transparency of most LCAs included in this review, full identification of the sources of discrepancies (methods applied, assumed production conditions) is not possible. Overall it can be concluded that the environmental impact of the electrolytic hydrogen production process is mainly caused by the GWP of electricity supply. For future environmental impact studies on hydrogen production systems, it is highly recommended to (i) divide the whole system into well-defined subsystems using compression as the final stage of the LCA and (ii) to provide energy inputs/GWP results for the different subsystems.